Influencia de la selección por competencia en la adaptabilidad laboral en el Departamento de Servicio al Cliente - Call Center del Banco Diners Club, Quito 2021 - Garzón Andrade, Caroline Mishell (2021)
The goal of this study is to establish the influence of competency-based personnel selection on labor adaptability in the Customer Service less Call Center department of Banco Diners Club Ecuador, focusing mainly on turnover and job performance. Since the selection process makes it possible to add new talents to the organization, it becomes a key task within the internal processes; it starts with the generation of the need to fill a position, giving way to the recruitment process and preselection of the most suitable candidates to fill the vacancy and later apply the selection tools. The tools will depend on the model adopted by the organization and will, in the end, allow the incorporation of the new employee. Once the employee is part of the organization it is possible to assess if the selection process was optimal based on performance results, turnover rates, among others. The Human Resources department of Banco Diners provided information for this study on the employees of the Customer Service less Call Center department regarding the selection process, demographic and performance data. With this information, an analysis was carried out showing that competency-based selection does directly affect the department's labor adaptability.